GAMELAN SELAP - PADA WAYANG GOLEK SUNDA - Sopandi, Caca (Paraguna, 2015)
The show of wayang golek purwa in Sunda has under gone considerable creativities by using gamelan selap as  the karawitan element. The use  of gamelan selap by the puppeteers  in the show of   waang  golek purwa becomes so phenomena that its background  needs to be known. Gamelan selap is created as  the fulfillment of laras/surupan  which  has not been fulfilled so that there  is an innovation  in  the instruments  which produce several series of tones as  the  new formation. Gamelan selap  is also used as  the puppeteer 's attraction to get market opportu nities.  This is proven by the  increase  ownership of gamelan selap by the groups  of wayang golek purwa   in   West  Java.    Nevertheless, the   use  of  gamelan  selap   has weakness  on  percussion   technique  problems, especially   on  the   bar instrument.  At Gamelan   selap  the  tones   can  be automatically  stepping passes through  three or even four tones.  The organological improvements are  therefore  required   in  order  the  use gamelan  selap  really  brings significant changes, not only for  the  benefit of working on the  composition but also for the sake of aesthetics.